Closing the Confidence Gap : A Behavioral Finance Perspective on Women’s Equity-Market Participation in India - Jain, Pranamya A.; K., Ashalatha (Indian Journal of Finance, 2026)
Purpose : India crossed 150 million Demat accounts in March 2025, yet women remain under-represented (≈ 24% of new Demat openings in Fy2025). This piece diagnosed the main constraints behind women’s lower participation in equities and mutual funds and proposed actions to close the gap. Methods : This article engaged in a perspective-style synthesis drawing on official statistics (SEBI, AMFI, RBI, OECD, World Bank), secondary reports, peer-reviewed studies, and cross-country program examples. Key Findings : Women’s participation trails market deepening: women contributed 30.5% of SIP assets and are reported at 14% of direct-equity assets under management (AUM) and 24% of mutual funds AUM. The primary bottleneck was framed as a financial literacy–confidence nexus: Literacy matters, but lower confidence and “permission-seeking” norms impede acting on knowledge; behavioral factors (stereotype threat, loss salience) and product complexity further reinforce the gap. Cross-country contrasts suggested defaults (auto-enrolment) and lifecycle education can materially narrow gender gaps. Originality : It shifted the policy focus from information deficits alone to confidence and agency, and proposed a five-pillar roadmap: School curriculum integration, opt-out workplace defaults for women, “gender-smart” adviser certification, SHG-based investment circles, and a national gender investing dashboard with quarterly reporting.